Impact of mental illness diagnosis on the course of mental health treatment : thematic analysis of service users’ experience - Ragnheiður Helga Sæmundsdóttir 1986- (2018)
The objective of this study was to analyze how a diagnosis of depression and/or anxiety impacts the course of mental healthcare at the outpatient unit of Landspitali-The National University Hospital of Iceland. The aim was twofold. Firstly, to gain understanding of how service users experienced various aspects of the assessment process and the course of treatment and secondly, their personal experience of getting a diagnosis in terms of attitude, emotional reaction and behavior. Data was collected through medical records and audio recorded, semi-structured interviews were conducted with 11 participants individually, all of whom had been diagnosed with anxiety or depression (or co-occurrence of both) between 2010 and 2012. Responses were investigated by applying an in-depth thematic framework analysis to the interview transcripts. In total, 26 themes were identified, including four main themes, seven overarching sub-themes and 15 sub-themes, all presented in a descriptive framework. A particularly pervasive theme was postponement of seeking care and among other important themes in service users’ experience were barriers, stigma and validation. Lastly, clinical implications of the results are discussed.